The Effect of Evaluation and Supervision on Improving Quality in the Directorate of Drug Research of the West Java Regional Police - Ade Hermawan Mulyana; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Digital Business Management, 2026)
The expected objectives of this research are as follows The influence of evaluation on improving the quality of task implementation, the influence of supervision on improving the quality of task implementation and the simultaneous influence of evaluation and supervision on improving the quality of the organization in the Narcotics Research Directorate of the West Java Regional Police . The calculated t value of X 1 ( Evaluation ) is 5.603 , the t table value for N = 92 is 1.986 . So 5.603 > 1.986 , it is concluded that partially Evaluation (X1 ) has an effect on Organizational Quality (Y), the calculated t value of X2 ( Supervision ) is 11.497 , the t table value of N = 92 is 1.986 . So 11.497 > 1.986 , it is concluded that Supervision (X2 ) has an effect on the quality of the organization (Y). The ANOVA test of 190.541 is greater than the value of f table N = 92 of 2.70 or 190.541 > 2.70 significant 0.000 , so it is said that Evaluation (X1 ) and Supervision variables (X2 ) together have an effect on the quality of the organization (Y). The R Square value of 0.811 means that evaluation and supervision have an effect of 81.1 % on the quality of the organization while the remaining 18.9 % is influenced by other factors not examined by the author in this study.